(untitled) (Quinto Sol, 2019)
The article is an analysis of the relationship between trade unionism and Peronism in the post-1947 period and a description of the process of mobilization of railway workers prior to the strikes of the late 1950 and early 1951. It expounds on the effects produced by the nationalization of the railways in Argentina, in the union of the Railway Union and in its relationship with the Peronist government. In a detailed way, it analyzes the dispute over the union representation of a sector of the railway workers with the new Confederation of Civilian Personnel of the Nation, in a context of intensification of the internal conflict of the Peronist movement and, in parallel, of strengthening of the will of governmental order. To end this representation dispute, the railway union’s negotiations with the government included defining the position of the railroad leaders (and a large part of the leadership of the General Confederation of Labor) regarding the reform of the power plant’s statute, whose project included the faculty to intervene subsidiaries and the adoption of the Peronist doctrine.